Class act: The case for reforming Britain's class action regime - Stephen Dnes (Institute of Economic Affairs (IEA), 2025)
Recent years have seen sharp growth in the number and scale of class actions filed before the UK Competition Appeal Tribunal ('Tribunal'). Pending claims are worth an estimated 134 billion. There are 655 million claimants, that is, ten claims per person. On average, there is roughly one new class action every week. The sudden increase in the scope of claims raises questions about their quality. The strong economic case against hardcore cartels applies equally to private litigation, but there are also some more adventuresome cases which stray from true cases of economic harm. Such cases increase costs and could harm innovation. Three specific concerns arise: (1) Cases are not getting much money, even against hardcore cartels; (2) Some low-quality cases have crept in, but they are mixed up with stronger ones which ought not to be undermined by reform; (3) Cases are very slow. This paper explores five related policy options to address these three issues. They can be used together or in isolation to focus cases onto the stronger ones and away from the weaker ones. The proposals span several major aspects of the cases and would significantly focus their remit.
Keywords: 330; Civil law; Legal reform; United Kingdom; Zivilrecht; Rechtsreform; Großbritannien